Ketahanan Kewirausahaan dalam Kondisi Konflik dan Rentan serta Peran Kewirausahaan Mandiri Lulusan dalam Usaha Kecil: Studi Kasus pada Lembaga Pendidikan Tinggi di Indonesia - Lakamudi, Rahma Karnia; Souisa, Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Entrepreneurial resilience is a crucial factor for university graduates starting small businesses amid various economic, social, and political challenges in Indonesia. This study aims to analyze the entrepreneurial resilience of graduates in managing small enterprises and identify the factors influencing the success or failure of these businesses. Data were collected from 350 graduates who have started small businesses in sectors such as food, technology, and services, using questionnaires that address entrepreneurship training, curriculum relevance, practical skills, and access to capital. The results reveal that entrepreneurial resilience is influenced by internal factors such as self-confidence and determination, as well as external factors like economic and political stability. Additionally, graduates' preparedness to start and sustain small businesses is closely linked to practical skills acquired during their education. The study offers recommendations for enhancing entrepreneurship curricula at higher education institutions with a focus on skills that can be directly applied in the business world, along with providing better support facilities.